Naval Wargame Prototyping: Multiplayer Real-Time Strategy Game Simulation Using Unreal Engine - Nattawat Chavanit; Sukawit Bualoy; Samart Moodleah (My University, 2023)
We propose an integration framework for a wargame prototype using the modern game engine - Unreal Engine. This wargame functions as a simulation tool for strategy training, strategy testing, and simulating enemy forces like warships, aircraft, and weapons. Existing wargames come in proprietary and free versions. The former is often expensive and exclusive due to security reasons, while developing a functional wargame is complex, requiring various technological components such as a physics system and artificial intelligence (AI). To overcome these challenges, we propose a rapid prototype using Unreal Engine. This approach leverages advanced technology and ensures the prototype is ready for future upgrades when new versions of the game engine are released. We evaluate the prototype's system capabilities and expert assessments.
Keywords: Artificial Intelligence in Games; Educational Games and Gamification; Robotic Path Planning Algorithms